ANALISIS PENGARUH STRATEGI POSITIONING TERHADAP KEPUTUSAN PEMBELIAN PADA KONSUMEN SEPEDA MOTOR HONDA (STUDI KASUS PADA PT.TUNAS DWIPA MATRA CABANG PAYUNG, BANGKA SELATAN) - Lestari, Sinta; Ruben Manullang, Rizal; Medinal (Jurnal Progresif Manajemen Bisnis, 2019)
This is an undergraduate thesis was written and compiled by Sinta Lestari with student identification number 560150056, entitled Bahasa Indonesia; “Analisis Pengaruh Strategi Positioning Terhadap Keputusan Pembelian Pada Konsumen Sepeda Motor Honda (Studi Kasus Pada PT. Tunas DwipaMatra Cabang Payung, Bangka Selatan)". The theories used in this study are Management theory, Marketing theory, Strategy Management theory, Positioning theory, and Purchasing Decision theory. The research method used purposive sampling method. Research respondents were consumers who bought Honda Motorcycles at PT. Tunas Dwipa Matra Cabang Payung, Bangka Selatan. The variables used are Product Attributes, Product Benefit, Application and Use, Competitors, and Prices as independent variables and Purchasing Decisions on Honda Motorcycle Consumers at PT. Tunas Dwipa Matra Cabang Payung, Bangka Selatan, as a dependent variable. Based on the results of the study that : (1) There is a significant effect of the variable Product Attibutes towards the Decision of Purchasing a Honda Motorcycles. This statement has been proved by the value of t-count (3,375) > t-tabel (1, 98861). (2) There is a significant effect of the Product Benefit variable towards the Decision of Purchasing a Honda Motorcycles, which has been stated by the value of t-count (7,127) > t-tabel (1,98861). (3) There is a significant influence on the variables of the Application and Use towards Decisions on the Purchasing a Honda Motorcycles at PT. Tunas Dwipa Matra Cabang Payung, Bangka Selatan. Thisis proven value thitung (-6,942) > ttabel (1,98861). (4) There is a significant influence of the Competitor variables on the Decision of Honda Motorcycle Purchases at PT. Tunas Dwipa Matra Cabang Payung, Bangka Selatan ( by the value of t-count (6,859) > t-tabel 1,98861). (5) There is a significant effect of the Price variable on the Decision of Purchasing a Honda Motorcycle (t-count 2,342 > t-table 1,98861) and lastly there is (6) a significant effect of Product Attributes, Product Benefits, Application and Use, Competitors, and Prices simultaneously towards the Decision of Purchasing a Honda Motorcycles at PT. Tunas Dwipa Matra Cabang which is has been prove by the value of F-count (31,9) greater than F-Table (2,33).